DEVELOPMENT OF LOGICAL COMPETENCES OF FUTURE PRIMARY SCHOOL TEACHERSDEVELOPMENT OF ELECTRONIC METHODOLOGICAL SUPPORT - Olimov Bakhriddin Jalal ogli (American Journals, 2025)
This article is based on a creative approachdevelopment of logical competencies of future primary school teachersImproving electronic methodological supportThe methodology and, as a consequence, effective methods for developing logical competencies of future primary school teachers are described.
Keywords: Creative, cognitive, logical competence, logical thinking, development, professional staff, ability to think, creativity.